STUDI EKSPLORATIF KINERJA GURU MATEMATIKA SELAMA PANDEMIC COVID-19 PADA SEKOLAH MENENGAH KEJURUAN (SMK) DI PERBAUNGAN - Eka Mayastika Sinaga (Jurnal AKTUAL, 2022)
The purpose of this study was to find out how the performance of mathematics teachers in vocational secondary schools during the Covid-19 Pandemic. The sampling technique used in this study is purposive sampling. The research method used is qualitative data method. Data Collection techniques used in this study were Observation, Interviews and Documentation of five schools. The determine the teacher’s performance, testing was carried out through an interactive analysis tool consisting of three types of activities that occurred simultaneously, namely Data Reduction, Data Presentation and Conclusing Drawing. Based on the results of the discussion obtained from this research 1) The teacher’s obstacle in the online learning process during the Covid-19 pandemic at the Perbaungan City Vocational High School, the main factor that is more important is the lack of facilities owned by students when studying online because not all students have a laptops or smartphones as online learning media.besides that another factor is internet quota which can not be reached by all students. Efforts are being made to minimize the obstacles experienced by teachers and student during the Covid-19 pandemic, namely conducting offline learning (outside the network) or offline with students and making innovations in the online learning process during the Covid-19 pandemic.  Keywords: Teacher Performance,Online Learning, Covid-19 Pandemic.